Right to Shelter an Expanded form of Right to Life and Personal Liberty: An Analysis - Sharma, Bhavana (International Journal of Psychosocial Rehabilitation, 2019)
Housing is one of the primary necessities of the civilised society. It has been declared as a basic Human Rights in UDHR, ICESCR, CEDAW, CRC & CERD. The Part III of Indian Constitution provides various Fundamental Rights but it does not expressly guarantee ‘Right to Shelter’ to citizen or non-citizen. Supreme Court of India has expanded the scope of right to life and personal liberty by inserting ‘Right to Shelter’ as a fundamental right under Article 21 of Indian Constitution. This research paper will analyze the emerging scenario of right to shelter in India by analysing how the Supreme Court of India interpreting the Constitution to provide the Social Justice to its citizens.